Optimising time samples for determining area under the curve of pharmacokinetic data using non‐compartmental analysis. (14th August 2019) - Hughes, Jim H.; Upton, Richard N.; Reuter, Stephanie E.; Phelps, Mitch A.; Foster, David J.R.
Abstract: Objectives: The selection of sample times for a pharmacokinetic study is important when trapezoidal integration (e.g. non‐compartmental analysis) is used to determine the area under the concentration–time curve (AUC). The aim of this study was to develop an algorithm that determines optimal times that provide the most accurate AUC by minimising trapezoidal integration error. Methods: The algorithm required initial single individual or mean pooled concentration data but did not specifically require a prior pharmacokinetic model. Optimal sample intervals were determined by minimising trapezoidal error using a genetic algorithm followed by a quasi‐Newton method. The method was evaluated against simulated and clinical datasets to determine the method's ability to estimate the AUC. Key findings: The sample times produced by the algorithm were able to accurately estimate the AUC of pharmacokinetic profiles, with the relative AUC having 90% confidence intervals of 0.919–1.05 for profiles with two‐compartment kinetics. When comparing the algorithm with rich sampling (e.g. phase I trial), the algorithm provided equivalent or superior sample times with fewer observations. Conclusions: The creation of the algorithm and its companion web application allows users with limited pharmacometric or programming training can obtain optimal sampling times for pharmacokinetic studies.